Tempo de desenvolvimento e caracterização morfológica de Zaeucoila unicarinata ashmead (hymenoptera: figitidae) sobre larvas de liriomyza sativae (diptera: agromyzidae) - Cunha, Rayane Sley Melo da (2021)
Zaeucoila unicarinata Ashmead (Hymenoptera: Figitidae) is a natural enemy of leaf miners Liriomyza sativae Blanchard (Diptera: Agromyzidae). Although Z. unicarinata contributes to the biological control of L. sativae, development and morphology of the immature stages of this solitary endoparasitoid are still unknown. The morphological changes experienced during the immature stages of endoparasitoids occur within the host's body, which is why they are still unknown in several species. Thus, studies aiming to know the development time and the morphology of the immature stages can help in a better understanding of the bioecology of this parasitoid. In addition, these informations are important for basic studies on the bioecology of Z. unicarinata and even for planning its mass creation. Given this, the objective of this study was to know development time and tocharacterize morphologically the immature stages of Z. unicarinata, raised in larvae of L. sativae. Daily, plants of Cucumis melo L. with leaves infested with larvae of second instar of L. sativae were exposed to parasitism. Then, the plants were placed in a cold chamber B.O.D. (Biochemical Oxigen Demand), under temperature conditions of 25 ± 2ºC, relative humidityof 60 ± 10% and photophase of 12 hours. Every 24 hours, 30 parasitized larvae / pupae were dissected during the period of development of the parasitoid, in order to record development time and the morphological characteristics of the immature phases (egg, larva, pre-pupa and pupa). The frequencies of the different stages of development of Z. unicarinata were calculated to define the number of larval instars. A Leica S8APO stereomicroscope with 80x magnification was used to observe all immature stages of Z. unicarinata. The complete development of the immature phases of the parasitoid lasted 22 days: egg (duration ≅ 4 days);larval instars - first (≅ 2 days), second (≅ 2 days), third (≅ 4 days) and fourth (≅ 2 days); pre- pupa (≅ 2 days) and pupa (≅ 6 days). Morphological characteristics: The eggs have an elongated shape, with a discreet peduncle; 1st and 2nd instar larvae are eucoiliform ranging from 0.62 mm to 1.14 mm of average length, 3rd and 4th instar larvae are hymenopteriform and measure 1.54 mm and 1.56 mm of average length, respectively. Pupae have a well- defined head, chest and abdomen with an average of 1.46 mm in length. The results obtained are important insofar as they allow to know the development and the morphological characteristics of the immature stages of Z. unicarinata, which will contribute to further studies on this parasitoid